Formation, Transmission, and Dynamic Evolution of a Multidrug-Resistant Chromosomally Integrated Plasmid in Salmonella Spp. - Chang, Man-Xia; Zhang, Jing; Zhang, Jin-Fei; Ding, Xiao-Min; Lu, Yang; Zhang, Jie; Li, Ruichao; Jiang, Hong-Xia (Frontiers in Microbiology, 2022)
IncHI2 plasmids, possessing high flexibility and genetic plasticity, play avital role in acquisition and transmission of resistance determinants. Polymorphic mobile genetic elements generated by a chromosomally integrated IncHI2 plasmid in an individual Salmonella isolate have not yet been detected, and the mechanisms of the formation, excision, and dynamic evolution of a multidrug-resistant chromosomally integrated plasmid (MRCP) have remained obscure. Herein, we identified a 260 kb blaCTX-M-55-qnrS1-bearing IncHI2 plasmid within a Salmonella Muenster strain. Plenty of heterogeneous mobile genetic elements (new E. coli chromosomally integrated plasmid or circular plasmids with different profiles) were yielded when this MRCP was conjugated into E. coli J53 with a transfer frequency of 10-4 to 10-5 transconjugants per donor. Bioinformatic analysis indicated that replicative transposition and homologous recombination of IS26 elements were particularly active, and the truncated Tn1721 also played a vital role in the formation of MRCP offspring. More importantly, when released from the chromosome, MRCP could capture and co-transfer adjacent-chromosomal segments to form larger plasmids progeny than itself. Stability and growth kinetics assays showed that the biological characteristics of MRCP progeny were differentiated. This study provides insight into a flexible existence of MRCP. The conversion between vertical and horizontal transmission endowed MRCP with genetic stability as a chromosomal coding structure and transferability as extra-chromosomal elements. This alternation may accelerate the acquisition and persistence of antibiotic resistance of clinical pathogens, and enhance their ability to respond to adverse environments, which poses a great challenge to the traditional antibiotic treatment.